2021
DOI: 10.1002/jmv.27446
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by real‐time PCR of five transport and conservation mediums of nasopharyngeal swab samples to COVID‐19 diagnosis in Santiago of Chile

Abstract: Due to the COVID-19 pandemic, many transport kits have been manufactured to preserve and transport nasopharyngeal swab samples (NPSs) from patients. However, there is no information on the performance of the different virus transport media (VTM) used in COVID-19 diagnosis in the population of Santiago de Chile. We compared the RT-qPCR amplification profile of five different viral transport kit mediums, including DNA/RNA Shield™, NAT, VTM-N, Ezmedlab™, and phosphate-buffered saline (PBS), for NPSs from

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
3
10
0
2
Order By: Relevance
“…For instance, Penrod et al, 2021 evaluated five transport media (VTM (containing 29.5g/l tryptose phosphate, 5g/l gelatin, 10,000U/l penicillin, 10,000U/l streptomycin, 25μg/l Fungizone), Copan Universal Transport Medium™, Becton Dickinson Liquid Amies Elution Swab (Eswab) Collection/Transport System, Remel Microtest™ M4RT® Multi-Microbe Media, and sterile 0.9% (w/v) sodium chloride) and reported that they all had equivalent sensitivity/specificity in COVID-19 diagnosis. Similar findings were obtained by several other studies which confirmed that PBS and normal saline not only maintained the stability and integrity of viral RNA (for up to 1 month when stored at -80ºC and 7 days at 4ºC) but also provided results that matched those obtained from other media(3,7,9,10). On the contrary, a different study demonstrated conflicting results of viral samples in 0.9% (w/v) saline not performing as well as commercially available transport media over a 72-hour storage period, although comparisons in this study were of samples during stock outs of VTM with those where VTM was available, rather than for split or standardized samples(11).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…For instance, Penrod et al, 2021 evaluated five transport media (VTM (containing 29.5g/l tryptose phosphate, 5g/l gelatin, 10,000U/l penicillin, 10,000U/l streptomycin, 25μg/l Fungizone), Copan Universal Transport Medium™, Becton Dickinson Liquid Amies Elution Swab (Eswab) Collection/Transport System, Remel Microtest™ M4RT® Multi-Microbe Media, and sterile 0.9% (w/v) sodium chloride) and reported that they all had equivalent sensitivity/specificity in COVID-19 diagnosis. Similar findings were obtained by several other studies which confirmed that PBS and normal saline not only maintained the stability and integrity of viral RNA (for up to 1 month when stored at -80ºC and 7 days at 4ºC) but also provided results that matched those obtained from other media(3,7,9,10). On the contrary, a different study demonstrated conflicting results of viral samples in 0.9% (w/v) saline not performing as well as commercially available transport media over a 72-hour storage period, although comparisons in this study were of samples during stock outs of VTM with those where VTM was available, rather than for split or standardized samples(11).…”
Section: Introductionsupporting
confidence: 89%
“…On the contrary, a different study demonstrated conflicting results of viral samples in 0.9% (w/v) saline not performing as well as commercially available transport media over a 72-hour storage period, although comparisons in this study were of samples during stock outs of VTM with those where VTM was available, rather than for split or standardized samples(11). Furthermore, a recent report showed that PBS was less sensitive compared to other media such as DNA/RNA shield™, highlighting the need for further research to ascertain the stability of this alternative transport medium(3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A47532 and E, N, and RdRp gene for Allplex™ 2019-nCoV Assay, Seegene, Seúl, South Korea. Cat, No RP10244Y) as previously reported by our group ( 13 ) and other authors ( 14 , 15 ). The detection of virus-specific mutations by Real-Time RT-PCR kit (Bioneer, Daejeon, South Korea.…”
Section: Diagnostic Assessmentsupporting
confidence: 66%
“…Samples were transported to the Universidad de Santiago Laboratory in a viral transport medium (GenoSur, Chile). Total RNA was extracted as previously described [ 8 ]. The detection of SARS-CoV-2 was carried out using the ORF1ab gene probe (TaqMan™ 2019nCoV Assay Kit v1 (Thermo Fisher Scientific, Reference code: A47532) using a one-step strategy as previously reported by our group [ 8 ].…”
Section: Methodsmentioning
confidence: 99%